REDES CONECTADAS: O ENSINO-APRENDIZAGEM DE MILLENNIALS EM LÍNGUA INGLESA - GUASTALLI, GABRIELA PERES (2019)
This study aims at investigating the network of connections between the Millennial generation (1982-2000) and technology in the English-language teaching-learning process through complexity. In this context, this research delves into the English language teaching-learning trajectory of teachers and students from generation Millennial through their narratives, in order to understand the pathways of this generation into learning and teaching a second language from their individual reflections. The theoretical framework of this research is based on the complexity thinking (Morin, 2005, 2008, Freire, M. 2009) and is developed in an articulated way with the concepts of technology in teaching-learning (Prensky, Azevedo, 2015) and English language teaching and learning (Paiva, 2015). This study is based on the qualitative approach in consonance with the narrative inquiry developed by Clandinin and Connelly (2015), as well as from the perspective of the hermeneutic conversation based on the perceptions of Gadamer (2004). The research seeks to critically reflect on how the past and present of the teaching-learning process of this generation in a second language can contribute to a future that favors the triad teacher, student and machine, with the human being at the center of the process. The results point out to the necessity of having a critical eye at mechanization of the teaching process in detriment to the students' needs, highlighting the importance of building a teacher-student connection in the teaching-learning process of a second language so that it can become meaningful, opening the frontiers for future discussions.